Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.7547/1030471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonslip Socks on the Gait Patterns of Older People When Walking on a Slippery Surface

Abstract: Background: Slips are a common cause of falls, and nonslip socks have been marketed to prevent slips in older people. However, few studies have investigated the biomechanical and clinical effects of walking in nonslip socks. This study aimed to examine gait parameters in older people walking on a slippery surface wearing nonslip socks compared with standard sock and barefoot conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
0
5
1
Order By: Relevance
“…While previous studies found that non-slip socks [ 9 ] and slip-resistant shoes [ 11 , 12 ] did not significantly change the FFCA at heel strike, this study showed that participants walked with an increased percentage of FFCAs within the targeted range during the use of and after using the FFCA feedback system, indicating that participants could use this feedback system as a training device to adjust their FFCA and walking patterns. In this study, verbal instruction was also effective at reducing FFCA; however, verbal instruction had limitations at the lower range of the targeted FFCA, leading to an excessively small FFCA with a mean value of less than 10°.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…While previous studies found that non-slip socks [ 9 ] and slip-resistant shoes [ 11 , 12 ] did not significantly change the FFCA at heel strike, this study showed that participants walked with an increased percentage of FFCAs within the targeted range during the use of and after using the FFCA feedback system, indicating that participants could use this feedback system as a training device to adjust their FFCA and walking patterns. In this study, verbal instruction was also effective at reducing FFCA; however, verbal instruction had limitations at the lower range of the targeted FFCA, leading to an excessively small FFCA with a mean value of less than 10°.…”
Section: Discussioncontrasting
confidence: 72%
“…To prevent slips and falls, multiple interventions have been developed to improve the contact surface between foot and ground, such as non-slip socks and footwear modifications. However, the effectiveness of non-slip socks on slip-prevention remains unclear [ 9 ]. A recent systematic review reported that insoles (e.g., orthopedic, textile, or vibrating insoles) generally improve static and dynamic balance, but may not be able to address the environmental risk factor of a slippery floor [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available socks (Baleno Co. Ltd., Hong Kong, China) was used to simulate reduced plantar sensory input [ 42 , 43 ]. Mechanoreceptors at the plantar surface detect changes in plantar pressure distribution resulting from body motion, and initiate postural reflexes which help prompt the human body to more stable postures [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mechanoreceptors at the plantar surface detect changes in plantar pressure distribution resulting from body motion, and initiate postural reflexes which help prompt the human body to more stable postures [ 44 ]. Previous studies have pointed that aging, diabetic malletis, and wearing socks reduced the cutaneous sensation of the plantar surface of the feet, and consequently led to balance disorders [ 42 , 43 , 45 ]. The socks were 1.6 mm thick, and made of 80.6% cotton, 16.7% polyamide and 2.7% Spandex.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we used standard cotton socks as the control condition; we acknowledge that non-slip socks may be preferable for older people who prefer not to wear shoes indoors [41] .…”
Section: Indoor Footwear and Balance And Gait Patterns In Older Womenmentioning
confidence: 99%